Pengaruh Hidro-Aroma Terapi Terhadap Kenyamanan Pada Pasien Gagal Jantung - Huwaina Af’idah (Jurnal Ventilator, 2023)
Heart failure is a pathophysiological condition where the heart's function as a pump is no longer able to meet the need for blood throughout the body for tissue metabolism (Price, 2015). This situation causes a decrease in cardiac output which can cause comfort problems based on clinical manifestations such as tightness, pain, heart palpitations, a feeling of coldness in the peripheral area, even swelling, muscle stiffness, numbness, and other subjective feelings felt by the patient himself. is defined as a disturbance of comfort because it is difficult for someone to determine the feeling they are experiencing so that the use of the word comfort is more appropriate to describe the feelings experienced by the patient so it is appropriate that in this condition there is a disturbance of comfort in the patient (Potter & Perry, 2014). The aim of this study was to determine the effect of hydro-aromatherapy on comfort in Heart Failure patients. This research method is a quasi-experimental pre test and post test with two groups, namely the intervention and control groups. Research data collection was carried out during September 2023 at the Integrated Heart Center (PJT) RSUP.H. Adam Malik Medan. The number of respondents with a diagnosis of CHF that met the study inclusion and exclusion criteria was 32 patients. In the intervention group, they were given a warm water foot soak mixed with aromatherapy oil, while in the control group they only soaked their feet in warm water. Measurement of comfort level uses the "daisy comfort scale" or the numerical daisy comfort intensity scale (Kolcaba, 2000). The results of this study showed that there was a significant difference in effect on increasing comfort levels (p<0.005) in the intervention group by soaking feet in warm water mixed with aromatherapy oil (p=0.000). Conclusion: The results of this study indicate that soaking feet in warm water mixed with aromatherapy oils in heart failure patients can increase comfort.